NATURE CONSCIOUSNESS IN THE POETRY OF SUMITRANANDANPANT: सुमित्रानंदनपंत के काव्य में प्रकृति-चेतना - Rani, Manju (International Journal of Research -GRANTHAALAYAH, 2015)
The environment is the basis of life on our earth, which is the basis for the emergence, development and survival of not only human but also different kinds of fauna and flora. The environment has an important role in the progress that human has made from the development of civilization to the present age, and it would not be an exaggeration to say that the development of human civilization and culture is the result of similar and harmony of human environment, that is why many ancient civilizations have adverse environment Due to the collapse of the era, many species and species of plants have become extinct and this crisis is increasing in many. In fact, the environment is not a single element but a group of many elements and all these elements or components, in a state of natural equilibrium, create an environment in which the development of human, animal, flora, etc., continues uninterrupted. But if any one of these elements is deficient or its natural activity is obstructed, then it also has a bad effect on the other elements, due to which a new odd situation is born. This asymmetry adversely affects climate, flora, fauna and humans. Which becomes the cause of crisis for the existence of world. पर्यावरण हमारी पृथ्वी पर जीवन का आधार है, जो न केवल मानव अपितु विभिन्न प्रकार के जीव जन्तुओं एवं वनस्पति के उद्भव, विकास एवं अस्तित्व का आधार है। सभ्यता के विकास से वर्तमान युग तक मानव ने जो प्रगति की है उसमें पर्यावरण की महती भूमिका है और यह कहना अतिश्योक्ति न होगी कि मानव सभ्यता एवं संस्कृति का विकास मानव पर्यावरण के समानुकूल एवं सामन्जस्य का परिणाम हैं यही कारण है कि अनेक प्राचीन सभ्यतायंे प्रतिकूल पर्यावरण के कारण काल के गर्त में समा गई तथा अनेक जीवों एवं पादप समूहों की प्रजातियाँ विलुप्त हो गयी और अनेक पर यह संकट गहराता जा रहा है। वास्तव में पर्यावरण कोई एक तत्व नहीं है अपितु अनेक तत्वों का समूह है और ये सभी तत्व अथवा घटक एक प्राकृतिक सन्तुलन की स्थिति में रहते हुए एक ऐसे वातावरण का निर्माण करते है जिसमें मानव, जीव-जन्तु, वनस्पति आदि का विकास अनवरत चलता रहे। किन्तु यदि इनमें से किसी एक भी तत्व में कमी आ जाती है अथवा उसकी प्राकृतिक क्रिया में अवरोध आ जाता है तो उसका बुरा प्रभाव दूसरे तत्वों पर भी पड़ता है, जिससे एक नई विषम परिस्थिति का जन्म होता है। इस विषमता से जलवायु, वनस्पति, जीव जन्तु एवं मानव पर प्रतिकूल प्रभाव पड़ता है। जो जीव जगत के अस्तित्व के लिये संकट का कारण बन जाता है।